Przeciwdziałanie koncentracji mediów w wybranych państwach członkowskich i Unii Europejskiej – analiza rozwiązań prawnych - Jas-Koziarkiewicz, Marta; Stasiak-Jazukiewicz, Ewa (Przegląd Politologiczny, 2018)
The problem of media ownership is crucial in democratic countries because the quality of the public debate depends on it. The aim of this analysis is to identify different forms of media ownership in six European countries (Austria, the Czech Republic, France, Germany, Hungary and Italy) and the means by which these countries prevent the concentration of media ownership. Since the decisions made by the European Union have a great impact on the European media, the article also presents the position of the EU on the concentration of media ownership, as well as its response to decisions taken by member states regarding this matter. The 2000s and 2010s saw the liberalization of national regulations on the concentration of media ownership in some states. Attempts were also made to limit the relationship between the media and politics. There is also an emerging tendency towards integrated regulation, which includes both the media and the telecommunication markets.